Satisfaction of medical students with the artistic anatomy lecture: A questionnaire study - Karaca Bozdağ, Zekiye; Çandır Gürses, Buse Naz (The European Research Journal, 2025)
Objectives: The aim of this study is to evaluate the effects of an artistic anatomy lecture on medical students and to identify the role of the lecture in education. Methods: A 20-question online satisfaction survey was administered to 32 out of 45 medical students who attended the artistic anatomy lecture at our university in the fall semester of 2023-2024. In the survey, questions were asked to reveal the students’ performance regarding the relationship between art and anatomy. SPSS Statistics 22 software (IBM SPSS, Turkey) was used for statistical analysis of the data obtained, and P<0.05 was considered statistically significant. Results: Ninety-three point eight percent of students stated that the artistic anatomy lecture contributed to their understanding of the relationship between art and anatomy. Survey results indicated that 87.5% of participants reported the lecture improved their observational skills, while 81.3% said it enhanced their clinical observation skills. In addition, 90.6% of the participants stated that the lecture helped them to understand the importance of art in medical education. Conclusions: The results show that the artistic anatomy lecture supports the development of important skills such as visual memory, analytical thinking and observational skills in medical students. In line with the literature, arts-based educational approaches enable students to gain an interdisciplinary perspective and develop the ability to pay attention to detail in clinical practice. We suggest that our findings may be useful for integrating artistic anatomy lectures into the curriculum of medical education, and may provide guidance to anatomists in this regard.